Pengembangan instrumen kualitas layanan dosen universitas swasta menggunakan pemodelan Rasch - Yuyun Elizabeth Patras; Rais Hidayat (Jurnal Konseling dan Pendidikan, 2020)
This research aims to get a research instrument, namely quality service lecturer at private university. The research method used mixed methods consists of literature reviews, interviews with students, expert validation, and a test use Rasch modeling. Literature review is carried out to obtain a description of the service quality according to the developing theory. Interviews with students aim to obtain items of review that fit the research context. Expert validation aims to obtain content validity. Collecting data through a questionnaire instrument containing 32 items. The number of respondents was 543 students at Pakuan University. The finding that 31 items of valid lecturer service quality instrument and one (1) item that is invalid must be discarded; This lecturer service quality instrument is very reliable because it has a reliability value above 0.9, both in terms of people reliability, alpha cronbach and item reliability. However, based on the item difficulty level test using item measure, item dimensionality and variable map, and Item: DIF test found several items that must be corrected.